Enhancement of High Order Multipole Fields in Optical Nanoantennas (Bulletin of Pure and Applied Sciences – Physics, 2021)
We have studied a mathematical framework of higher-order multipole fields in the vicinity of  optical nanoantennas. We have exemplified at suitably chosen Nanoantennas i.e. a Nano  antenna which strongly enhances the quadruple field. The modification of excitation rates in  quantum mechanical systems due to this quadrupolar enhancement was studied. The hybrid  system consisting of an optical Nano antenna and a quantum mechanical three level system  was studied in detail. A properly designed Nano-antenna can excite dipole for bidden  transitions in three level systems due to the enhanced higher order multipole fields. The  dynamics of the system is strongly altered by the presence of the nanoantenna and cannot be  done by the quadrupolar enhancement alone. This can be achieved by enhancing higher order  multipole fields near the antenna. A quadrupole transition as the dominant excitation channel  in a three level system was considered. It was found that the enhancement of this transition  significantly intensify subsequent emission processes with respect to altered emission  characteristics. The effects depend on geometrical parameters; the properties of the optical  nanoantenna can be tailored and hence allowed for direct implementations in spectroscopies  schemes. The obtained results were found in good agreement with previously obtained  results.